A longitudinal investigation of the relationship between maternal mind-mindedness and theory of mind - Kirk, Elizabeth; Pine, Karen; Wheatley, Lisa; Howlett, Neil; Schulz, Joerg; Fletcher, Ben (C) (British journal of developmental psychology, 2015)
Data are presented from a longitudinal investigation examining the relationship between maternal mind‐mindedness (MM) in infancy and socio‐cognitive development in childhood. We revisited children (n = 18) who had taken part in a longitudinal study as infants. MM had been assessed at 10, 12, 16, and 20 months of age. We followed up these children at 5–6 years of age to test their higher order theory of mind (ToM) (using the strange stories task). The convergent validity, temporal stability, and predictive validity of the construct of MM were examined in a longitudinal data set. The five measures of MM were not significantly correlated. Mother's production of appropriate mind‐related comments (but no other measures) showed evidence of temporal stability throughout infancy. Thus, MM (as measured by appropriate mind‐related comments) was confirmed as a stable construct. Children's ToM at 5–6 years of age was significantly predicted by their mother's MM up to 4 years earlier, with MM accounting for 40% of the variance of the strange stories task scores. These findings identify a relationship between MM across a protracted period of infancy and socio‐cognitive development at 5–6 years of age.